Role of Propionibacterium Acnes in Sarcoidosis: A Meta-analysis - Zhou, Ying; Hu, Yang; Li, Huiping (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Purpose: To evaluate the available molecular evidence on the possible role of Propionibacterium acnes (P. acnes) in the development of sarcoidosis, the meta-analysis was performed. Methods: Case-control studies from January 1980 to October 2012 on P. acnes associated with sarcoidosis were searched.Overall odds ratios (OR) and 95% confidence intervals (CI) were obtained. Results: Nine studies were selected, which included 458 cases and 438 controls. 359 samples from 458 patients were positive with a positive signal rate of 78.4% (33.3% to 92.3%). Significantly elevated sarcoidosis risk was associated with P. acnes (OR = 19.58, 95% CI = 13.06 - 29.36). There was no evidence of publication bias. Conclusions: The present data and meta-analysis supports an association between P. acnes and some cases of sarcoidosis.